2020
DOI: 10.1590/0102-672020190001e1503
|View full text |Cite
|
Sign up to set email alerts
|

Does Evolutionary Biology Help the Understanding of Metabolic Surgery? A Focused Review

Abstract: Introduction: The wide net of physiological issues involved in metabolic surgery is extremely complex. Nonetheless, compared anatomy and phisiology can provide good clues of how digestive tracts are shaped for more or less caloric food, for more or less fiber, for abundance and for scarcity. Objective: To review data from Compared Anatomy and Physiology, and in the Evolutionary Sciences that could help in the better comprehension of the metabolic surgery. Method: A focused review of the literature selecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
0
12
0
8
Order By: Relevance
“…Alguns autores sugeriram que a ressecção do estômago distal provoca alterações nos níveis de certos níveis de hormônios gastrointestinais que modificariam a pressão do EEI 26 . Outros argumentam que a lesão da membrana frenoesofágica, bem como alterações do ângulo esofagogástrico (His) relacionadas à reconstrução da continuidade gastrointestinal, podem alterar a função esfincteriana 4,14,19,22,23 , alguns atribuindo a origem dessa disfunção do EEI ao tipo de reconstrução, seja do tipo Billroth I ou II 4,11 .…”
Section: /4unclassified
“…Alguns autores sugeriram que a ressecção do estômago distal provoca alterações nos níveis de certos níveis de hormônios gastrointestinais que modificariam a pressão do EEI 26 . Outros argumentam que a lesão da membrana frenoesofágica, bem como alterações do ângulo esofagogástrico (His) relacionadas à reconstrução da continuidade gastrointestinal, podem alterar a função esfincteriana 4,14,19,22,23 , alguns atribuindo a origem dessa disfunção do EEI ao tipo de reconstrução, seja do tipo Billroth I ou II 4,11 .…”
Section: /4unclassified
“…besity is defined as a metabolic disease in which the accumulation of adipose tissue has a proportion of body mass higher than normal, consisting of the fastest growing disease in Brazil and establishing itself as a major health problem 8 .According to the Brazilian Association for the Study of Obesity and Metabolic Syndrome, the data reveal that more than 50% of the Brazilian population is overweight and in children the prevalence is 15% 17 . In the Unified Health System of Brazil (SUS) the number of bariatric operations increased, only between 2008 and 2017 it grew 215%, according to data from the Brazilian Society of Bariatric and Metabolic Surgery 1 .…”
Section: Introduction Omentioning
confidence: 99%
“…T he prevalence of obesity has increased in the last decade and several prospective cohort studies have shown that obese people, defined by body mass index (BMI), are at increased risk of arterial hypertension and cardiovascular disease as well as of mortality from these causes 18,23 . In addition, the distribution of fat deposits, such as visceral abdominal adipose tissue (VAT), regardless of general obesity, has been associated with cardiometabolic risks 11 and others 5 .…”
Section: Introductionmentioning
confidence: 99%